Most of what you know about addiction is wrong - Kala, Anirudh; Ambedkar, Atul (fwd.) (New Delhi Speaking tiger books, 2023)
In Most of What You Know About Addiction is Wrong, distinguished psychiatrist Anirudh Kala debunks common myths on the largely misunderstood topic of addiction. The book introduces readers to the ways in which humankind has been engaging with addictive substances over time and our complicated ongoing relationship with them.
Keywords: Drug; Pharmacodynamics